Alpha-Lipoic Acid and Antioxidant Diet Help to Improve Endothelial Dysfunction in Adolescents with Type 1 Diabetes: A Pilot Trial. (16th June 2015) - Scaramuzza, Andrea; Giani, Elisa; Redaelli, Francesca; Ungheri, Saverio; Macedoni, Maddalena; Giudici, Valentina; Bosetti, Alessandra; Ferrari, Matteo; Zuccotti, Gian Vincenzo
Abstract : After evaluating the prevalence of early endothelial dysfunction, as measured by means of reactive hyperemia in adolescents with type 1 diabetes, we started a 6-month, double-blind, randomized trial to test the efficacy of an antioxidant diet (± alpha-lipoic acid supplementation) to improve endothelial dysfunction. Seventy-one children and adolescents, ages 17 ± 3.9 yrs, with type 1 diabetes since 9.5 ± 5.3 yrs, using intensified insulin therapy, were randomized into 3 arms: (a) antioxidant diet 10.000 ORAC + alpha-lipoic acid; (b) antioxidant diet 10.000 ORAC + placebo; (c) controls. BMI, blood pressure, fasting lipid profile, HbA1c, insulin requirement, dietary habits, and body composition were determined in each patient. An antioxidant diet significantly improved endothelial dysfunction when supplemented with alpha-lipoic acid, unlike diet with placebo or controls. A significant reduction in bolus insulin was also observed. We speculate that alpha-lipoic acid might have an antioxidant effect in pediatric diabetes patients by reducing insulin.